1993
DOI: 10.1289/ehp.93101s327
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2-aminofluorene by human polymorphonuclear leukocytes: more evidence for the association between inflammation and cancer.

Abstract: Recent investigations have demonstrated the ability of leukocytes to metabolize promutagens or procarcinogens into their genotoxic forms. As a possible explanation for the association between inflammation and cancer, we and others have hypothesized that local accumulations of leukocytes could take up nearby promutagens, metabolize them, and release genotoxic agents that may cause damage in the surrounding tissue. Using a modified, two-step preincubation protocol with Salmonella, we have tested this hypothesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…88,90 Therefore, Bhosale et al 88 suggested that experiments involving in 1.3 (PRO) should be performed in the dark to avoid the formation of photooxidation products. [105][106][107] It is important to note that 1.5 (2AF) is oxidized by cytochrome P450 enzymes to the more active electrophilic agent, N-hydroxy-2-aminofluorene (N-OH-2-AF) and then HOSO 2 O-NH-2-AF under the action of sulfotransferase or N-acyltransferase. They are both considered the most likely to attack the nucleophilic positions in DNA such as C8-arylamine-dG, C8-arylamine-dA, and the amino group of deoxyguaninosine as depicted in Figure 1 The level of 1.8 (PhIP) in food varies greatly depending on type of food and cooking method.…”
Section: Purification Of Bilirubinmentioning
confidence: 99%
“…88,90 Therefore, Bhosale et al 88 suggested that experiments involving in 1.3 (PRO) should be performed in the dark to avoid the formation of photooxidation products. [105][106][107] It is important to note that 1.5 (2AF) is oxidized by cytochrome P450 enzymes to the more active electrophilic agent, N-hydroxy-2-aminofluorene (N-OH-2-AF) and then HOSO 2 O-NH-2-AF under the action of sulfotransferase or N-acyltransferase. They are both considered the most likely to attack the nucleophilic positions in DNA such as C8-arylamine-dG, C8-arylamine-dA, and the amino group of deoxyguaninosine as depicted in Figure 1 The level of 1.8 (PhIP) in food varies greatly depending on type of food and cooking method.…”
Section: Purification Of Bilirubinmentioning
confidence: 99%